EFL PRE-SERVICE TEACHERS’ PERCEPTION IN TEACHING ENGLISH PROCESS DURING KAMPUS MENGAJAR PROGRAM - Rizka Ananda Bin Ladi; Robi Soma (Universitas Jambi, 2023)
Kampus Mengajar program as one of Merdeka Belajar-Kampus Merdeka (MBKM) programs initiated by the Minister of Education and Culture of the Republic of Indonesia in 2020 is one of the programs that aims to provide opportunities for students to learn and develop themselves through activities outside the classroom. Therefore, this study aims to explore the perception of EFL Pre-service Teachers’ Perception in Teaching English Process during Kampus Mengajar Program. By using a qualitative descriptive method, five Pre-service teachers of the English Education study program at University of Jambi were interviewed as alumni of Kampus Mengajar program batch 4. The data were analyzed by using data reduction, data display and verification developed by Miles and Huberman (1994). The results of this study, there were also many problems faced by the participants such as lack of experience in teaching, lack of facilities for teaching, difficulties with students’ abilities in learning English, and difficulties with the school location. Despite that, there were also some strategies used by the participants to overcome those problems such as maximizing preparations for teaching English process, have backup plan for the facilities, learnt to know students’ needs, and leaving early if the school is far away.